An approach to the simultaneous quantitative analysis of metabolites in table wines by 1H NMR self-constructed three-dimensional spectra. (1st February 2017) - Li, Bao Qiong; Xu, Min Li; Wang, Xue; Zhai, Hong Lin; Chen, Jing; Liu, Jin Jin
Highlights: A novel approach was proposed to the analysis of wines based on 1 H NMR spectra. The chemical shifts and overlapped peaks no longer need to be calibrated in this work. The interferences such as noise and non target compounds became insignificant. The quantitative determination of multi-components was successfully implemented. The proposed approach could extend the application of conventional 1 H NMR. Abstract: Wine consists of several hundred components with different concentrations, including water, ethanol, glycerol, organic acids and sugars. Accurate quantification of target compounds in such complex samples is a difficult task based on conventional 1 H NMR spectra due to some challenges. In this paper, the three-dimensional spectrum was constructed firstly by simply repeating 1 H NMR spectrum itself so as to extract the features of target compounds by Tchebichef moment method. A proof-of-concept model system, the determination of five metabolites in wines was utilized to evaluate the performance of the proposed strategy. The results indicate that the proposed approach can provide accurate and reliable concentration predictions, probably the best results ever achieved using PLS and interval-PLS methods. Our novel strategy has not only good performance but also does not require laborious multi-step and subjective pretreatments. Therefore, it is expected that the proposed method could extend the application of conventional 1 H NMR.